Conversor CC-CC boost intercalado de alto ganho de tensão acionado por DSP - Vieira, Mateus Pacheco (2018)
This work presents a DC-DC high gain boost interleaved topology built with output film capacitors in order to be used for supplying non-linear loads and is modulated by a DSP programmed with Simulink blocks. The studied converter can supply single phase and three phase inverters. The interleaving technic in DC-DC converters requires a much lower output capacitance, allowing the use of film capacitors, whose life-time is twice bigger than the electrolytic capacitors. Based on the studied converter, qualitative and quantitative analisys were performed. The quantitative analisys was used to develop a project example with 1 kW power, 60 V input voltage, and 400 V output voltage. An prototype was built based on the project for experimental results harversting. The experimental results were properly compared to simulation results and theoretical waveforms. The experimental results validated the proposed converter, because its waveforms were similar to the ones documented in the theoretical analisys.